Out of plane bending in curved pipes. - Madureira, M.L.R. (2011)
Piping structures have large application in power generation and chemical plants. Given their complexity and construction safety standards, the development of accurate numerical methods has been analyzed by several authors [1,2,3] with trigonometric solutions. Also pipe finite elements, with a considerable amount and complexity of work, has been used to define accurate models for numerical approach of the stress field [4,5,6,7]. In this work both analytical and numerical approaches are presented. A mathematical analytical solution is derived using a mixed formulation where unknown functions are combined with Fourier series [8]. Using a minimization criterion for the total energy involved in the process a system of second order ordinary differential equations is obtained and then solved using the MAPLE® mathematical package. Numerical simulation was performed using the Finite Element Method for the same steel pipe under out-of-plane bending and results are compared showing that a good agreement can be reached with only a few terms in the Fourier expansion. In this example four terms were considered.